Conserved genetic regions across angiosperms as tools to develop single‐copy nuclear markers in gymnosperms: an example using cycads. (5th March 2014) - Salas‐Leiva, Dayana E.; Meerow, Alan W.; Francisco‐Ortega, Javier; Calonje, Michael; Griffith, M. Patrick; Stevenson, Dennis W.; Nakamura, Kyoko
Abstract Several individuals of the Caribbean Zamia clade and other cycad genera were used to identify single‐copy nuclear genes for phylogeographic and phylogenetic studies in Cycadales. Two strategies were employed to select target loci: (i) a tblastX search of Arabidopsis conserved ortholog sequence (COS) set and (ii) a tblastX search of Arabidopsis‐Populus‐Vitis‐Oryza Shared Single‐Copy genes (APVO SSC) against the EST Zamia databases in GenBank. From the first strategy, 30 loci were selected, and from the second, 16 loci. In both cases, the matching GenBank accessions of Zamia were used as a query for retrieving highly similar sequences from Cycas, Picea, Pinus species or Ginkgo biloba. After retrieving and aligning all the sequences in each locus, intron predictions were completed to assist in primer design. PCR was carried out in three rounds to detect paralogous loci. A total of 29 loci were successfully amplified as a single band of which 20 were likely single‐copy loci. These loci showed different diversity and divergence levels. A preliminary screening allowed us to select 8 promising loci (40S, ATG2, BG, GroES, GTP, LiSH, PEX4 and TR) for the Zamia pumila complex and 4 loci (COS26, GroES, GTP and HTS) for all other cycad genera.